Avaliação de serviços ecossistêmicos e ambientais na RESEX marinha de Mocapajuba - CARMO, Mattheus Correa do (2018)
Due ecosystem and environmental services aren’t quantified in real monetary terms, they are not taken into account when political decisions are made, thereby threatening the life sustainability on the planet. Thus, this study seeks to evaluate ecosystem and environmental services from a technical view associated with environmental perception. Located in the municipality of São Caetano de Odivelas, northeastern of Pará State, the inhabitants of this reserve are characterized as extractive peoples, who depend on artisanal fishing and shellfish for their survival. The data were obtained from the application of questionnaires and interviews in 5 (five) distinct communities, in the socioeconomic and environmental spheres, where the socioeconomic profile and their empirical knowledge about ecosystem and environmental services were surveyed. In addition, to determine the economic importance of services, a experimental methodological proposal based on the Value Links concept was used in order to carry out an environmental valuation of the area used in the oysters farming. It was observed that the socioeconomic aspects of the communities, as well as the activities developed and the knowledge on the ecosystem and environmental services are directly associated with their geographical position. The population interviewed presents a local and non-global view of RESEX's estuarine environment. Thus, the related perceptions are about the tide entrance, saline intrusion, climatic variations and spatial distribution of mangroves. The communities closest to the municipal headquarters are the least dependent on RESEX resources. While the farthest community, situated upstream of the Mojuim estuary, differs totally from other regions. In a single community, the Pereru de Fatima, the practice of oyster farming was shown to promote social and economic benefits. This region of 5.4 ha was valued at R $ 65, 000.00, but this value does not reflect the totality of ecosystem and environmental services in the region.